2018
DOI: 10.12740/app/82020
|View full text |Cite
|
Sign up to set email alerts
|

Is flexibility always associated with mental health? A study of coping and depression

Abstract: Aim of the studyThe present study aimed to determine if there is indeed a relationship between coping flexibility, defined as an ability to use a greater variety of coping strategies, and depression scores in patients suffering from major depressionSubject or material and methodsThe participants of this study were clinical patients undergoing cognitive behavioural therapy (CBT). The sample was taken from the cognitive-behavioural therapy arm of Jacobson’s landmark study (1996, 2008). Depression was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Behavioral inflexibility that includes impairments in reversal learning, is a common feature of many psychiatric illnesses and neurodegenerative disorders such as schizophrenia, attention-deficit/hyperactivity-disorder (ADHD), drug addiction, depression, Parkinson's or Huntington's diseases (Owen et al, 1992;Lawrence et al, 1999;Swainson et al, 2000;Cools, 2001;Rogers and Robbins, 2001;McLean et al, 2004;Fillmore and Rush, 2006;Waltz and Gold, 2007;Murray et al, 2008;Clark et al, 2009;Shell et al, 2018). Along with brain impairments associated with these diseases, a large literature has shown that across species, the frontal lobe and the basal ganglia (BG) play fundamental roles in enabling the different aspects of behavioral flexibility (Kirkby, 1969;Kolb, 1977;Pisa and Cyr, 1990;Owen et al, 1992;Eslinger and Grattan, 1993;Roberts et al, 1994;Wise et al, 1996;Dias et al, 1996Dias et al, , 1997Birrell and Brown, 2000;Swainson et al, 2000;Collins et al, 2000;Monchi et al, 2001;Cools, 2001;Crofts et al, 2001; Barense et al, 2002;Chudasama and Robbins, 2003;McLean et al, 2004;Ragozzino, 2007;Waltz and Gold, 2007;Floresco et al, 2008).…”
mentioning
confidence: 99%
“…Behavioral inflexibility that includes impairments in reversal learning, is a common feature of many psychiatric illnesses and neurodegenerative disorders such as schizophrenia, attention-deficit/hyperactivity-disorder (ADHD), drug addiction, depression, Parkinson's or Huntington's diseases (Owen et al, 1992;Lawrence et al, 1999;Swainson et al, 2000;Cools, 2001;Rogers and Robbins, 2001;McLean et al, 2004;Fillmore and Rush, 2006;Waltz and Gold, 2007;Murray et al, 2008;Clark et al, 2009;Shell et al, 2018). Along with brain impairments associated with these diseases, a large literature has shown that across species, the frontal lobe and the basal ganglia (BG) play fundamental roles in enabling the different aspects of behavioral flexibility (Kirkby, 1969;Kolb, 1977;Pisa and Cyr, 1990;Owen et al, 1992;Eslinger and Grattan, 1993;Roberts et al, 1994;Wise et al, 1996;Dias et al, 1996Dias et al, , 1997Birrell and Brown, 2000;Swainson et al, 2000;Collins et al, 2000;Monchi et al, 2001;Cools, 2001;Crofts et al, 2001; Barense et al, 2002;Chudasama and Robbins, 2003;McLean et al, 2004;Ragozzino, 2007;Waltz and Gold, 2007;Floresco et al, 2008).…”
mentioning
confidence: 99%
“…In addition, there are few studies on the relationship between flexibility and mental health. Some studies believe that the improvement of flexibility can help patients with developmental delays to improve their psychological state ( Shell et al, 2018 ). Our results show that flexibility cannot predict the mental health of adolescents aged 12–13, and the relationship between flexibility and mental health of different ages and specific populations is not well defined.…”
Section: Discussionmentioning
confidence: 99%
“…Rigidity has also been considered as the antithesis to variability. To study variability or rigidity, measures of ways of coping with stressful events (e.g., problem-solving, support seeking, positive thinking) have been gathered and responses have been configured to reflect breadth in the use of coping strategies in general or across different stressful situations (a larger coping repertoire; Bonanno et al, 2020;Fresco et al, 2006;Keng et al, 2018;Lam & McBride-Chang, 2007;Lester et al, 1994;Shell et al, 2018;Zimmer-Gembeck et al, 2013. Related approaches have been referred to as the breadth of a coping repertoire, a balanced profile of coping (Cheng et al, 2014) or as directed coping (Wright, 2020).…”
Section: Conceptualizing Coping Flexibilitymentioning
confidence: 99%